AN ANALYSIS OF THE FISCAL CAPACITY OF DISTRICT AND CITY GOVERNMENTS IN THE EAST NUSA TENGGARA PROVINCE - Maria Odriana Veronica Moi; Susano P. Baso; Ilyona Risty (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to analyze the fiscal capacity of districts and cities in East Nusa Tenggara Province through the analysis of the degree of decentralization and fiscal capacity index. Data were analyzed using the degree of fiscal decentralization formula and the calculation of the fiscal capacity index. The results showed that on average, districts and cities in East Nusa Tenggara Province have a low degree of decentralization of 7.99% and are in the very low fiscal capacity index category of 0.442-0.515. The largest contribution to the allocation of regional expenditure comes from central government transfer funds.